(untitled) (Ibrahim Cardiac Medical Journal, 2017)
The association of Wilson’s disease (WD) with autoimmune hepatitis (AIH) has rarely been documented. The difficulties in differential diagnosis of WD and AIH have seen specially in the paediatric population. Children with WD specially in younger ones, may have clinical features indistinguishable from autoimmune hepatitis. We report a case of 8-year old girl child who presented with jaundice, anaemia, leg oedema and arthritis. Ultimately the patient was diagnosed as a case of WD with AIH after meticulous investigation. Treatment was started with prednisolone, d-penicillamine and subsequently prednisolone was tapered with addition of azathioprine. D-penicillamine was stopped, with clinical and biochemical improvement and zinc was added to continue life-long. Follow up after 8 months of initial treatment she was non anaemic and non-icteric. Her leg oedema and arthritis also subsided. Liver biochemistry returned to normal level. It is important therefore to recommend strongly a thorough screening for AIH in patients with initial diagnosis of WD and also screening for WD for patients presenting with AIH. So a combined therapy may be of early benefit. Ibrahim Card Med J 2015; 5 (1&2): 72-74